The Impact of Complex Strength Training on Special Strength and Some Snatch Holds for Young Greco-Roman Wrestlers - Samer Mahdi Saleh (Sinar Sport Journal, 2025)
In the last couple of decades, mankind has seen much progress in many fields of life, especially in sports. This is exemplified by the amazing levels of skills and scores we hear about across different types of sports. Wrestling is an open-ended sport where teaching and training have unique attributes, facilitating a requirement for specialized teaching and training, particularly after the recent changes in international rule in terms of technical performance of the Greco-Roman wrestling. Development of complicated strength training and its effect on specific strength and some snatch holds in Greco-Roman wrestlers in experimental and control groups. The researcher applied the experimental method to two groups (experimental and control) on a sample of young Greco Roman wrestlers aged 19-20 years from Al-Rafidain Club for the year 2025. Those were four weight classes, which include two wrestlers for each of the four weight classes (55, 60, 66, and 74 kg). They had an experimental group and a control group (two groups). From those weight classes, four wrestlers from each formed into groups. Specific strength levels and skill performance (drawing hold, over-the-chest throw, snatch, and other holds) were matched for the two groups. The complexity of strength training for (8) weeks included (3) training units per week for each group, with a total of (24) training units (Kanda). The researcher concluded improvement in the specific strength and skills in pull grip : over the chest throw grip (snatch) : Kanda grip in busting the performance levels through complex strength exercises had a significant positive effect to the experimental group than the traditional exercises in controlling group based on the results.